Th17/Regulatory T cells ratio evolution: A prospective study in a group of healthy pregnant women. (February 2022) - Braga, A.; Neves, E.; Guimarães, J.; Braga, J.; Vasconcelos, C.
Highlights: Prospective observational study where peripheral blood lymphocyte subsets were analyzed in each trimester of pregnancy. We observed a consistent reduction in peripheric Treg cell while the Th17 cell count remained stable. The Th17/Treg ratio increases significantly throughout pregnancy to the postpartum period. This data could explain why systemic syndromes like preeclampsia develop during the second half of pregnancy. This data help to explain why many autoimmune disorders flourish in the first weeks postpartum. Abstract: During pregnancy, the maternal immune system is challenged to tolerate a semi-allogenic fetus. A shift toward a tolerogenic profile is essential to ensure a healthy fetal and placental development. One of the most important mechanisms involved in the maternal immune tolerance towards the fetal antigens is expressed in the activity of the regulatory T (Treg) and Th17 cells. The behavior and equilibrium of these two T lymphocyte populations were rarely studied in normal healthy pregnancies through the beginning of gestation to the postpartum period. We conducted a prospective longitudinal observational study where peripheral blood lymphocyte subsets were analyzed in each trimester of pregnancy and postpartum period in a group of healthy pregnant women. Our study observed a consistent reduction in peripheric Treg cell count through all pregnancy while the Th17 cell count remained stable. The Th17/Treg ratio increases significantly throughout pregnancy to the postpartum period. These changes could be justified by the migration of the immunotolerant Treg cells to the maternal decidua and lead to the establishment of a systemic pro-inflammatory profile by the end of pregnancy. This data could explain why systemic syndromes like preeclampsia develop in susceptible women during the second half of pregnancy or why many autoimmune disorders flourish in the first weeks postpartum.